Bridging prehistoric caves with buried landscapes in the Swabian Jura (southwestern Germany). (20th August 2018) - Barbieri, Alvise; Leven, Carsten; Toffolo, Michael B.; Hodgins, Gregory W.L.; Kind, Claus-Joachim; Conard, Nicholas J.; Miller, Christopher E.
Abstract: The Ach and Lone valleys of the Swabian Jura represent two key areas for the study of the dispersal of modern humans into central Europe, owing to the presence of numerous cave sites in the region that contain stratigraphic sequences spanning the Middle and Upper Paleolithic. However, despite the relatively complete sequences contained within these caves, previous studies hypothesize that phases of erosion have influenced the preservation of Upper Paleolithic deposits, particularly those dating to the Gravettian. Furthermore, these same studies suggest that during the Late Glacial and Holocene, colluvial sediments subsequently covered these unconformities. In this paper we present a dataset that helps us evaluate how geomorphological processes active at the regional scale around the Last Glacial Maximum (LGM) have impacted the preservation of the archaeological record within the cave sites of the Ach and Lone valleys. To this end we applied and integrated a variety of methods, including geophysical prospection, coring, micromorphology, Fourier Transform infrared (FTIR) spectroscopy, and radiocarbon dating. Our results show that alternating phases of soil formation, hillside denudation, river valley incision and floodplain aggradation have been the major processes active in Lone and Ach valleys throughout the Pleistocene and Holocene. These processes impacted the formation histories of the caves in the two valleys, thereby significantly influencing how we interpret the archaeological record of the region. In particular our data support the hypothesis arguing for the erosion of Gravettian-aged deposits (which are dated between 29.000 and 27.000 14 C BP) from the caves of Bockstein, Hohle Fels and possibly Hohlenstein-Stadel. Shortly after this erosive phase, increased depositional rates of loess nearly free of gravel and reworked soils marked in both the Ach and Lone valleys a shift towards colder and drier conditions corresponding with the LGM. Deteriorating climate likely forced Gravettian groups to abandon the Swabian Jura. The Magdalenian recolonization of the region took place in a cool interstadial (13.500–12.500 14 C BP) that was followed by a period of climate deterioration with minor phases of erosion in the caves and bedrock denudation. Towards the beginning of the Holocene the accumulation of frost debris ( Bergkies ) at the cave entrances marked the cessation of erosion within the caves.